Capsaicin inhibits the migration, invasion and EMT of renal cancer cells by inducing AMPK/mTOR-mediated autophagy. (1st October 2022) - Que, Taotao; Ren, Bingyi; Fan, Yizeng; Liu, Tianjie; Hou, Tao; Dan, Weichao; Liu, Bo; Wei, Yi; Lei, Yuzeshi; Zeng, Jin; Li, Lei
Abstract: Capsaicin (CAP), extracted from Capsicum fruits, has been reported to exhibit antitumor effects in various lines of cancer cells. However, the mechanism underlying its antitumor efficiency is not fully understood. Autophagy is a fundamental self-degradation process of cells that maintains homeostasis and plays a controversial role in tumor initiation and progression. The EMT is defined as a system regulating cells transformed from an epithelial-like phenotype into a mesenchymal phenotype by several internal and external factors, following the metastatic performance of the cells developed. The present study aimed to investigate the potential role of autophagy in CAP-induced antitumor effects in renal cell carcinoma (RCC) 786-O and CAKI-1 cell lines. The results revealed that CAP remarkably inhibited the migration and invasion of RCC cells in vitro and metastasis in vivo. Moreover, we found that the CAP treatment increased the formation of autophagolysosome vacuoles and LC3 yellow and red fluorescent puncta in RCC cells and upregulated the expression of LC3, suggesting that autophagy was induced by CAP in 786-O and CAKI-1 cell lines. Our further results demonstrated that CAP-induced autophagy was mediated by the AMPK/mTOR pathway. In conclusion, our study provides new knowledge of the potential relationship between autophagy and metastasis inhibition induced by CAP, which might be a promising therapeutic strategy in RCC. Highlights: Capsaicin inhibited renal cancer cells EMT and metastasis in vivo and vitro. Capsaicin inhibited EMT and metastasis by inducing autophagy in RCC. Capsaicin induced autophagy via activating AMPK/mTOR signal pathway.